Analysis Of Problematics In Arabic Language Morphology To Understand Mufradat In The Learning of The Quran and Hadith at Mts Teungku Chik Pante Kulu Aceh Besar District - Afriati, Intan (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Teaching Arabic vocabulary morphology at MTs Teungku Chik Pante Kulu, Aceh Besar District is an integral part of the Islamic Religious Education (PAI) curriculum, especially in the context of learning the Qur'an and Hadith as one of the science groups in PAI. However, PAI teachers who teach the Qur'an and Hadith subjects often face various problems that affect the effectiveness of teaching and student understanding. This analysis aims to identify and understand these problems and their impact on the quality of learning. This type of research uses a qualitative method with a field research approach. Data collection techniques by conducting observations and interviews. The results of the study indicate that: 1). The problems of Arabic morphology for understanding the mufradat in the lessons of the Qur'an and Hadith at MTs Teungku Chik Pante Kulu, Aceh Besar District are as follows, namely: Limited Morphological Knowledge of Teachers, Ineffective Teaching Methods, Limited Resources and Teaching Materials, Difficult Curriculum Adjustments and Low Student Interest and Motivation. 2). The impact of the problems of Arabic morphology to understand the vocabulary in the Al-Quran and Hadith lessons are as follows, namely: Quality of Arabic language learning, student learning outcomes, student motivation and interest, effectiveness of learning and long-term impact on religious studies.